Penerapan Bahasa Persuasif dalam Mengikis Insecure Remaja di Kota Palu - Ulinsa Ulinsa; Ali Karim; Idris Pattekai; Efendi Efendi; Mutmainah Mutmainah (Badan Pengembangan dan Pembinaan Bahasa, 2023)
This research examines the implementation of persuasive language in eroding insecurity for youth in Palu City. From the perspective of adolescent psycholinguistics who experience insecurity teenagers who have high ideals and want a successful future. This research aims to; 1) describe the types of educational persuasive language in eroding insecure for adolescents in the city of Palu, 2) describe the causal factor of insecure wrong education for youth in Palu city, and 3) describe the results of implementing persuasive language in eroding insecure for youth in Palu city. This research is presented in a qualitative form. The instrument used in collecting data in this paper is a mobile phone recorder. The type of data in this paper is written data and the source of the data is obtained from oral and written utterances from researchers toward experienced adolescents insecure in the city of Palu. Data collection techniques are carried out through stages; 1) observation, 2) interview, and 3) documentation. Technical data analysis was carried out through the following stages: 1) data collection, 2) data reduction, 3) data classification, and 4) conclusion. The results of the study show that 1) types of persuasive language in education erode insecurity in adolescents in the city of Palu including (1) persuasive education to invite/persuade, (2) persuasive education to urge/order, and (3) persuasive education to influence. 2) causal factors insecure for adolescents in the city of Palu, namely (1) educating by pampering, (2) educating with violence, and 3) the results of implementing persuasive language in eroding insecure in adolescents in the city of Palu it was declared successful from the 20 youths who were sampled. Implementation of the use of persuasive language in eroding insecurity in adolescents in the city of Palu was declared successful because the 20 youths who were sampled it was stated that they were able to revive their self-confidence by showing self-confidence in the form of work. AbstrakPenelitian ini mengkaji implementasi bahasa persuasif dalam mengikis insecure bagi remaja di kota Palu. Dari perspektif psikolinguistik remaja yang mengalami insecure pada dasarnya remaja yang memiliki cita-cita yang tinggi dan menginginkan masa depan yang sukses. Penelitian ini bertujuan untuk; 1) mendeskripsikan jenis bahasa persuasif pendidikan dalam mengikis insecure bagi remaja di kota Palu, 2) mendeskripsikan faktor-faktor penyebab insecure pendidikan yang salah bagi remaja di kota Palu, dan 3) mendeskripsikan hasil implementasi bahasa persuasif dalam mengikis insecure bagi remaja di kota Palu. Penelitian ini disajikan dalam bentuk kualitatif. Instrumen yang digunakan dalam menggumpulkan data pada makalah ini adalah alat rekam telpon genggam. Jenis data pada makalah ini adalah data tertulis dan sumber data diperoleh dari tuturan lisan dan tulisan dari peneliti terhadap remaja yang mengalami insecure di kota Palu. Teknik pengumpulan data dilakukan melalui tahapan; 1) obesrvasi, 2) wawancara, dan 3) dokumentasi. Teknis analisis data dilakukan melalui tahapan :1) pengumpulan data, 2) reduksi data, 3) klasifikasi data, dan 4) penarikan kesimpulan. Hasil penelitian menunjukkan bahwa 1) jenis bahasa persuasif pendidikan dalam mengikis insecure pada remaja di kota Palu meliputi (1) persuasif pendidikan mengajak/membujuk, (2) persuasif pendidikan menghimbau/memerintah, dan (3) persuasif pendidikan memengaruhi. 2) faktor-faktor penyebab insecure bagi remaja di kota Palu, yakni (1) mendidik dengan memanjakan, dan (2) mendidik dengan kekerasan, dan 3) hasil implementasi bahasa persuasif dalam mengikis insecure pada remaja di kota Palu dinyatakan berhasil dari 20 orang remaja yang dijadikan sampel. Impelementasi pemanfaatan bahasa persuasif dalam mengikis insecure kepada remaja di kota Palu dinyatakan berhasil karena dari 20 orang remaja yang dijadikan sampel dinyatakan dapat memunculkan kembali rasa percaya dirinya dengan menunjukkan rasa percaya diri dalam bentuk karya.